Imperfect Competition, Trade Policies, and Technological Changes in the Orange Juice Market - Mahalingam Dhamodharan; Stephen Devadoss; Jeff Luckstead (Journal of Agricultural and Resource Economics, 2016)
Orange juice processors in Florida face stiff competition from São Paulo processors. The United States imposes a specific import tariff to protect domestic processors. São Paulo processors also export to the European Union, which imposes an ad valorem tariff on orange juice. Under oligopolistic competition with endogenous firm entry and exit, this paper analyzes how the changes in tariff policy and productivity impact the market structure in Florida and São Paulo; prices; quantities; and welfare in the United States, Brazil, and the European Union. Free trade and an increase in São Paulo productivity benefit U.S. and EU consumers and São Paulo processors. In contrast, U.S. tariff reduction adversely impacts Florida processors.